2015
DOI: 10.1111/ijfs.12784
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterisation of soya milk enriched with isoflavone aglycone fermented by lactic acid bacteria combined with hydrothermal cooking pretreatment

Abstract: A fermented soya milk (FSM) enriched with isoflavone aglycone (FSM-SPIA) was prepared from heated soya protein isolate (SPI)-isoflavone complex. After 48 h of fermentation, FSM-SPIA contained higher contents of living bacteria, free amino acids and aglycone compared with the FSM of SPI (FSM-SPI) and the FSM of SPI-isoflavone complex (FSM-Mix). In the in-vitro digestion experiment, FSM-SPIA showed higher antioxidant capacity and isoflavones (ISO) bioavailability than FSM-SPI and FSM-Mix. This was likely due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…After pepsin and trypsin digestion for 240 min, the nitrogen release reached to 80.75% and 81.21% for SPI-3d and SPI-5d, respectively, indicating excellent protein digestibility. These findings are well in agreement with previous studies (Yang et al, 2015). Bartkiene et al (2015) reported that compared to untreated sample, protein digestibility of fermented soya bean was found to be higher on average by 15.9%.…”
Section: In Vitro Digestibility Of Soya Bean Proteinsupporting
confidence: 93%
See 4 more Smart Citations
“…After pepsin and trypsin digestion for 240 min, the nitrogen release reached to 80.75% and 81.21% for SPI-3d and SPI-5d, respectively, indicating excellent protein digestibility. These findings are well in agreement with previous studies (Yang et al, 2015). Bartkiene et al (2015) reported that compared to untreated sample, protein digestibility of fermented soya bean was found to be higher on average by 15.9%.…”
Section: In Vitro Digestibility Of Soya Bean Proteinsupporting
confidence: 93%
“…After pepsin and trypsin digestion for 240 min, the nitrogen release reached to 80.75% and 81.21% for SPI‐3d and SPI‐5d, respectively, indicating excellent protein digestibility. These findings are well in agreement with previous studies (Yang et al ., ). Bartkiene et al .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations